Preparation method of zirconium-modified catalyst for gas-based direct reduction iron

By performing zirconium dioxide modification and high-temperature resistance test on gas-based direct reduction iron catalyst, the problem of poor high-temperature resistance in high-temperature environments is solved, and the efficient stability of the catalyst and zero nitrogen oxide emissions are achieved.

CN119425708APending Publication Date: 2025-02-14SHAANXI RELAISHITONG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411677249.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing gas-based direct reduction iron catalysts exhibit poor high temperature resistance under high temperature environments, which affects their use effect and activity stability.

Method used

By modifying the catalyst support by zirconium dioxide and performing high temperature resistance tests under high temperature conditions, the structure and composition of the catalyst are optimized to improve its stability and activity at high temperatures.

Benefits of technology

The catalyst's high temperature resistance is significantly improved, allowing it to maintain efficient catalytic performance under high temperature environments, extend its service life, and achieve zero emissions of nitrogen oxides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425708A_ABST
    Figure CN119425708A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a zirconium-modified catalyst for gas-based direct reduction iron. The preparation method comprises the following steps: S1, preparing a catalyst carrier; step 2, modifying with zirconium dioxide; step 3, dipping the active component nickel; 4, drying, roasting and decomposing the catalyst; 5, evaluating the activity and selectivity of the catalyst; and step 6, carrying out a high temperature resistance test on the catalyst. The catalyst for the gas-based direct reduction iron, which is high in conversion rate, good in catalytic effect and high-temperature-resistant, can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of iron and steel metallurgy, and in particular to a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron. Background Art

[0002] Gas-based direct reduced iron is a production process that reduces iron ore to produce metallic iron. Iron ore (such as hematite or magnetite) is reduced by gas (usually hydrogen or carbon monoxide) to produce metallic iron. This method has the following advantages over the traditional blast furnace ironmaking method:

[0003] Lower CO2 emissions: Natural gas can be used instead of coal;

[0004] Higher raw material utilization rate: able to effectively utilize low-grade iron ore;

[0005] Flexibility: can adapt to different raw materials and product requirements.

[0006] The use of catalysts in the process can further improve the reduction efficiency of the process, reduce the operating temperature and improve energy utilization. Catalysts can accelerate the reduction reaction of iron ore and reduce the temperature and time required for the reaction; they can significantly improve the reaction efficiency of the reducing gas through catalysis, thereby improving the utilization of hydrogen and carbon monoxide; they can adjust the reduction process of different iron ores to optimize the purity and recovery rate of the product and achieve the purpose of selective control.

[0007] How to achieve catalysts with better performance based on energy conservation and emission reduction is the main goal of technicians. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a zirconium-modified gas-based direct iron reduction catalyst, which can prepare a gas-based direct iron reduction catalyst with high conversion rate, good catalytic effect and high temperature resistance.

[0009] A technical solution to achieve the above object is: a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following steps:

[0010] S1: Preparation of catalyst support:

[0011] First, aluminum nitrate, magnesium nitrate and calcium nitrate are fully dissolved and added to a precipitation reaction tank, the temperature of the reaction tank is adjusted, and then a soda ash aqueous solution is slowly added under stirring conditions for neutralization reaction, and the end point PH is controlled to be 7.5-9.5, followed by filtering and washing; the filter cake is dried and then calcined for the first time; the calcined material is added with a release agent and then granulated and formed, and then calcined for the second time after forming to obtain a catalyst carrier precursor;

[0012] Step 2: Zirconium dioxide modification:

[0013] The catalyst carrier prepared in step 1 is placed in a prepared zirconium nitrate solution for carrier modification, and after the carrier modification is completed, the catalyst carrier is dried and calcined to decompose to obtain a modified catalyst carrier;

[0014] Step 3: Impregnation of active component nickel:

[0015] A mixed solution of nickel nitrate, cerium nitrate and lanthanum nitrate is prepared to obtain an impregnation solution, and a small amount of polyol solution is added to the impregnation solution; the catalyst carrier modified in step 2 is impregnated in the impregnation solution, so that the catalyst active component nickel and the catalyst promoter are loaded on the catalyst carrier;

[0016] Step 4: Drying and calcination of the catalyst:

[0017] The catalyst carrier loaded with nickel nitrate, cerium nitrate and lanthanum nitrate is dried, calcined and decomposed to obtain finished catalyst particles;

[0018] Step 5: The finished catalyst particles obtained in step 4 are crushed and sieved in a mortar, loaded into a fixed bed reactor, and the activity and selectivity of the catalyst are evaluated;

[0019] Step 6: Conduct a high temperature resistance test on the catalyst in a fixed bed reactor under high temperature conditions to evaluate the high temperature resistance of the catalyst by observing the formation of nickel aluminum spinel and the changes in nickel grains in a high temperature environment.

[0020] Preferably, in step 2, the concentration of Zr(NO3)4 in the zirconium nitrate solution is 200-600 g / l, the carrier modification time is 10-50 minutes, the calcination decomposition temperature is 300-600°C, and the calcination time is 1-8 hours.

[0021] Preferably, in step 3, the concentration of Ni(NO3)2 in the impregnation solution is 400-800 g / l, the concentration of Ce(NO3)3 is 100-200 g / l, and the concentration of La(NO3)3 is 80-150 g / l.

[0022] Preferably, the impregnation liquid contains 0.2-0.5 g / L of polyol.

[0023] Preferably, the polyol is one of ethylene glycol, propylene glycol, glycerol and butylene glycol.

[0024] Preferably, the impregnation liquid contains 0.3 g / L of propylene glycol.

[0025] Preferably, step 4 specifically includes:

[0026] Step 4.1, drying the catalyst using a chain plate drying furnace;

[0027] Step 4.2, using a hot air circulation double-channel mesh belt furnace to calcine and decompose the catalyst carrier loaded with nitrate, the double-channel mesh belt furnace includes channel A and channel B, channel A is a catalyst decomposition channel, channel B is a hot air circulation channel, which provides a heat source for catalyst decomposition, and the catalyst carrier loaded with nitric acid is calcined and decomposed in channel A, and the high-temperature nitrogen oxide gas generated in channel A is heat exchanged with the tube of channel B, and then enters the nitrogen oxide circulating water absorption device after compression, and the generated nitric acid aqueous solution is used to prepare nitrate solution to achieve zero emission of nitrogen oxides.

[0028] Preferably, a heat exchange tube is provided between channel A and channel B of the dual-channel furnace, and the heat exchange tube transfers the heat generated by heat exchange in channel B to channel A, thereby providing a heat source for decomposition of the catalyst in channel A.

[0029] Preferably, in step 5, the activity and selectivity evaluation of the catalyst specifically includes:

[0030] Step 5.1, heating the catalyst to 500°C under nitrogen, switching to feed gas and continuing to heat to 940°C, with the heating time being no less than 4 hours;

[0031] Step 5.2, sampling and analyzing the gas composition at the reactor outlet until it is stable;

[0032] Step 5.3, calculate the conversion rate of carbon dioxide and methane, and the selectivity of carbon monoxide and hydrogen; the conversion rate of carbon dioxide and methane indicates the activity of the catalyst, and the selectivity of carbon monoxide and hydrogen indicates the hydrogen yield of the catalyst and the anti-carbon stability of the catalyst.

[0033] Preferably, the raw gas consists of methane, carbon dioxide, carbon monoxide, steam, hydrogen and a small amount of nitrogen, wherein the volume percentage of CH4 is 10-15%, the volume percentage of CO2 is 10-15%, the volume percentage of CO is 17-19%, the volume percentage of H2O is 1-5%, the volume percentage of H2 is 40-50%, and the rest is N2.

[0034] The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron of the present invention has the following advantages:

[0035] 1. The catalyst is modified with zirconium dioxide to make it have better high temperature resistance, so that the catalyst can fully adapt to the high temperature in the furnace tube of the reducing gas preparation furnace, thereby improving the use effect of the catalyst;

[0036] 2. Zirconium dioxide itself has good high temperature resistance. For surface-modified catalysts, zirconium dioxide is mainly distributed on the surface of catalyst particles. It is not easy to form a eutectic with nickel, the active component of the catalyst, at high temperatures to reduce the activity of the catalyst.

[0037] 3. The addition of low-concentration polyols can make the Ni element tend to be enriched on the pore surface and enter the internal structure less, so that higher catalytic performance can be achieved with lower nickel loading;

[0038] 4. A double-channel furnace with a special structure is used to calcine and decompose the catalyst carrier loaded with nickel nitrate, which can recover the nitrogen oxide gas as nitric acid solution for reuse, thereby avoiding the discharge of nitrogen oxide gas into the atmosphere, greatly reducing environmental pollution, and achieving green and environmentally friendly production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a comparison chart of the conversion rates of carbon dioxide and methane of the catalysts obtained after adding propylene glycol solutions of different concentrations to the impregnation liquid for impregnation in Example 5;

[0040] Figure 2 This is Example 5, a comparison chart of the amount of nickel aluminum spinel and nickel grains of the catalyst obtained after impregnation with propylene glycol solutions of different concentrations added to the impregnation solution. DETAILED DESCRIPTION

[0041] In order to better understand the technical solution of the present invention, the following is a detailed description through specific embodiments:

[0042] Embodiment 1:

[0043] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0044] Step 1: Take 70% aluminum nitrate nonahydrate and 30% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 50°C, add a certain amount of deionized water to fully dissolve, then add it to the neutralization reaction tank, and then add a 15% mass concentration of sodium carbonate aqueous solution for neutralization precipitation, and control the end point pH value to 8.5. The precipitate is filtered and washed, and the filter cake is dried at 110°C for 12 hours, and then calcined. The calcination temperature is selected to be 400°C and the calcination time is 6 hours. Obtain an unmodified catalyst carrier powder.

[0045] The catalyst carrier powder obtained is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor. The release agent is one or more of graphite, rice husk powder, polyvinyl alcohol, and paraffin.

[0046] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 400g / l, the carrier modification time is 50 minutes, the calcination and decomposition temperature is 500°C, and the calcination time is 4 hours; a zirconium-modified catalyst carrier is obtained.

[0047] Step 3: The modified catalyst carrier is immersed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate immersion solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier. The concentration of Ni(NO3)2 in the mixed solution is 550g / l, the concentration of Ce(NO3)3 is 110g / l, and the concentration of La(NO3)3 is 150g / l. The immersion time is 60 minutes and the immersion temperature is 50°C.

[0048] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 480°C. The drying time is 10 hours, and the calcination time is 6 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0049] The mass percentage of the active component nickel in the obtained catalyst product is 15.1%, the mass percentage of CeO2 is 2.3%, the mass percentage of La2O3 is 1.3%, and the mass percentage of ZrO2 is 3.2%.

[0050] Step 5: Catalyst activity and selectivity evaluation

[0051] The catalyst particles were crushed in a mortar and sieved, and 200 ml of catalyst with a particle diameter of 2-2.5 ml was measured and loaded into a fixed bed reactor to evaluate the activity and selectivity of the catalyst. The diameter of the fixed bed reactor was 20 mm.

[0052] Evaluation conditions:

[0053] Heating time: 6 hours

[0054] Catalyst bed temperature: 940℃

[0055] The volume percentage composition of the raw gas is: methane (CH4) 13.4%, carbon dioxide (CO2) 13.3%, carbon monoxide (CO) 17.7%, steam (H2O) 2.75%, hydrogen (H2) 43.5%, and the rest is inert gas.

[0056] Raw gas flow rate: 4280ml / min.

[0057] The evaluation data table is as follows

[0058] Time, h 10 50 100 200 500 800 <![CDATA[CH4 conversion rate, %]]> 93.4 93.1 92.2 90.4 88.8 84.5 <![CDATA[CO2 conversion rate, %]]> 93.6 92.3 91.8 89.6 85.9 83.2 <![CDATA[H2 / CO]]> 1.66 1.65 1.62 1.62 1.62 1.61

[0059] Step 6: Place the catalyst in a fixed bed reactor, pass the raw gas, and conduct a 48-hour high temperature resistance test under high temperature conditions to evaluate the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst in a high temperature environment and the changes in nickel grains.

[0060] Nickel aluminum spinel refers to a new component without catalytic activity formed by the co-melting of the active component nickel of the catalyst and the aluminum oxide in the catalyst carrier at high temperature. The formation of nickel aluminum spinel will reduce the activity and service life of the catalyst. The change of nickel grains refers to the growth of nickel grains, the active component of the catalyst, as the temperature rises, thereby reducing the active surface of the catalyst and causing the catalyst activity to decrease.

[0061] The evaluation data table is as follows

[0062] Temperature, °C 800 850 900 950 1000 <![CDATA[NiAl2O4,%]]> -- -- 0.98 1.46 3.55 Ni grain, nm 26 36 48 55 77

[0063] Embodiment 2:

[0064] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0065] Step 1: Take 70% sodium aluminate and 30% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 50°C, add a certain amount of deionized water to fully dissolve, then add it to the neutralization reaction tank, and then add a 12% mass concentration of sodium carbonate aqueous solution for neutralization precipitation, and control the end point pH value to 8.5. The precipitate is filtered and washed, and the filter cake is dried at 110°C for 12 hours, and then calcined. The calcination temperature is selected to be 400°C and the calcination time is 6 hours. Obtain unmodified catalyst carrier powder.

[0066] The obtained catalyst carrier powder is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor.

[0067] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 400g / l, the carrier modification time is 50 minutes, the calcination and decomposition temperature is 500°C, and the calcination time is 4 hours; a zirconium-modified catalyst carrier is obtained.

[0068] The modified catalyst carrier of step 3 is placed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate impregnation solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier. The concentration of Ni(NO3)2 in the mixed solution is 550g / l, the concentration of Ce(NO3)3 is 110g / l, and the concentration of La(NO3)3 is 150g / l. During the impregnation process of the catalyst carrier, in order to better disperse the active component nickel grains, a small amount of propylene glycol solution is added to the impregnation solution, and the concentration of propylene glycol is 0.2g / L. The impregnation time is 60 minutes, and the impregnation temperature is 50°C.

[0069] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 480°C. The drying time is 10 hours, and the calcination time is 6 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0070] The mass percentage of the active component nickel in the obtained catalyst product is 15.1%, the mass percentage of CeO2 is 2.3%, the mass percentage of La2O3 is 1.2%, and the mass percentage of ZrO2 is 3.3%.

[0071] Step 5: Catalyst activity and selectivity evaluation

[0072] The catalyst particles were crushed in a mortar and sieved, and 200 ml of catalyst with a particle diameter of 2-2.5 ml was measured and loaded into a fixed bed reactor to evaluate the activity and selectivity of the catalyst. The diameter of the fixed bed reactor was 20 mm.

[0073] Evaluation conditions:

[0074] Heating time: 6 hours

[0075] Catalyst bed temperature: 941℃

[0076] The volume percentage composition of the raw gas is: methane (CH4) 13.4%, carbon dioxide (CO2) 13.3%, carbon monoxide (CO) 17.7%, steam (H2O) 2.75%, hydrogen (H2) 43.5%, and the rest is inert gas.

[0077] Raw gas flow rate: 4273ml / min.

[0078] The evaluation data table is as follows

[0079] Time, h 10 50 100 200 500 800 <![CDATA[CH4 conversion rate, %]]> 97.1 96.5 96.3 96.1 95.8 95.3 <![CDATA[CO2 conversion rate, %]]> 97.6 96.6 96.3 96.2 95.5 95.2 <![CDATA[H2 / CO]]> 1.66 1.65 1.62 1.62 1.62 1.61

[0080] Step 6: Place the catalyst in a fixed bed reactor, pass the raw gas, and conduct a 48-hour high temperature resistance test under high temperature conditions to evaluate the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst in a high temperature environment and the changes in nickel grains.

[0081] The evaluation data table is as follows

[0082] Temperature, °C 800 850 900 950 1000 <![CDATA[NiAl2O4,%]]> -- -- 0.11 0.32 0.40 Ni grain, nm 12 14 16 18 18

[0083] Embodiment 3:

[0084] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0085] Step 1: Take 75% aluminum nitrate and 25% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 60°C, add a certain amount of deionized water to fully dissolve, then add it to the neutralization reaction tank, and then add a 20% sodium carbonate aqueous solution for neutralization and precipitation, and control the end point pH value to 9.5. The precipitate is filtered and washed, and the filter cake is dried at 115°C for 10 hours, and then calcined. The calcination temperature is selected to be 450°C and the calcination time is 6 hours. Obtain unmodified catalyst carrier powder.

[0086] The obtained catalyst carrier powder is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor.

[0087] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 450g / l, the carrier modification time is 40 minutes, the calcination and decomposition temperature is 485°C, and the calcination time is 6 hours; a zirconium-modified catalyst carrier is obtained.

[0088] The modified catalyst carrier of step 3 is placed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate impregnation solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier, and the concentration of Ni(NO3)2 in the mixed solution is 450g / l, the concentration of Ce(NO3)3 is 120g / l, the concentration of La(NO3)3 is 140g / l, and the concentration of ethylene glycol is 0.3g / L. The impregnation time is 50 minutes and the impregnation temperature is 45°C.

[0089] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 485°C. The drying time is 10 hours, and the calcination time is 5 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0090] The mass percentage of the active component nickel in the obtained catalyst product is 14.8%, the mass percentage of CeO2 is 2.1%, the mass percentage of La2O3 is 1.1%, and the mass percentage of ZrO2 is 3.4%.

[0091] Step 5: Catalyst activity and selectivity evaluation

[0092] Evaluation conditions:

[0093] Heating time: 6 hours

[0094] Catalyst bed temperature: 941℃

[0095] The volume percentage composition of the raw gas is: methane (CH4) 13.7%, carbon dioxide (CO2) 13.8%, carbon monoxide (CO) 18.2%, steam (H2O) 2.7%, hydrogen (H2) 43.1%, and the rest is inert gas.

[0096] Raw gas flow rate: 4245ml / min.

[0097] The evaluation data table is as follows

[0098] Time, h 10 50 100 200 500 800 <![CDATA[CH4 conversion rate, %]]> 97.3 96.6 96.0 95.8 95.1 94.9 <![CDATA[CO2 conversion rate, %]]> 97.5 96.3 96.5 96.0 95.1 94.6 <![CDATA[H2 / CO]]> 1.67 1.66 1.63 1.63 1.62 1.62

[0099] Step 6: Place the catalyst in a fixed bed reactor, pass the raw gas, and conduct a 48-hour high temperature resistance test under high temperature conditions to evaluate the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst in a high temperature environment and the changes in nickel grains.

[0100] The evaluation data table is as follows

[0101] Temperature, °C 800 850 900 950 1000 <![CDATA[NiAl2O4,%]]> -- -- 0.10 0.31 0.38 Ni grain, nm 11 15 17 19 21

[0102] Embodiment 4:

[0103] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0104] Step 1: Take 75% sodium aluminate and 25% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 60°C, add a certain amount of deionized water to fully dissolve, then add to the neutralization reaction tank, and then add a 20% sodium carbonate aqueous solution for neutralization precipitation, and control the end point pH value to 9.0. The precipitate is filtered and washed, and the filter cake is dried at 110°C for 14 hours, and then calcined. The calcination temperature is selected to be 500°C and the calcination time is 8 hours. Obtain unmodified catalyst carrier powder.

[0105] The obtained catalyst carrier powder is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor.

[0106] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 375g / l, the carrier modification time is 45 minutes, the calcination and decomposition temperature is 500°C, and the calcination time is 6 hours; a zirconium-modified catalyst carrier is obtained.

[0107] The modified catalyst carrier of step 3 is placed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate impregnation solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier, and the concentration of Ni(NO3)2 in the mixed solution is 400g / l, the concentration of Ce(NO3)3 is 135g / l, the concentration of La(NO3)3 is 170g / l, and the concentration of glycerol is 0.4g / L. The impregnation time is 70 minutes and the impregnation temperature is 40°C.

[0108] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 480°C. The drying time is 10 hours, and the calcination time is 5 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0109] The mass percentage of the active component nickel in the obtained catalyst product is 15.6%, the mass percentage of CeO2 is 2.0%, the mass percentage of La2O3 is 1.1%, and the mass percentage of ZrO2 is 3.2%.

[0110] Step 5: Catalyst activity and selectivity evaluation

[0111] Evaluation conditions:

[0112] Heating time: 6 hours

[0113] Catalyst bed temperature: 940℃

[0114] The volume percentage composition of the raw gas is: methane (CH4) 13.8%, carbon dioxide (CO2) 13.6%, carbon monoxide (CO) 18.0%, steam (H2O) 2.5%, hydrogen (H2) 43.3%, and the rest is inert gas.

[0115] Raw gas flow rate: 4305ml / min.

[0116] The evaluation data table is as follows

[0117] Time, h 10 50 100 200 500 800 <![CDATA[CH4 conversion rate, %]]> 97.5 96.4 95.8 95.5 95.1 94.8 <![CDATA[CO2 conversion rate, %]]> 97.5 96.4 96.3 96.1 95.3 94.8 <![CDATA[H2 / CO]]> 1.68 1.67 1.64 1.63 1.63 1.62

[0118] Step 6: Place the catalyst in a fixed bed reactor, pass the raw gas, and conduct a 48-hour high temperature resistance test under high temperature conditions to evaluate the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst in a high temperature environment and the changes in nickel grains.

[0119] The evaluation data table is as follows

[0120] Temperature, °C 800 850 900 950 1000 <![CDATA[NiAl2O4,%]]> -- -- 0.12 0.29 0.39 Ni grain, nm 9 16 18 19 20

[0121] Embodiment 5:

[0122] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0123] Step 1: Take 70% sodium aluminate and 30% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 50°C, add a certain amount of deionized water to fully dissolve, then add it to the neutralization reaction tank, and then add a sodium carbonate aqueous solution with a mass concentration of 18% for neutralization precipitation, and control the end point pH value to 9.0. The precipitate is filtered and washed, and the filter cake is dried at 115°C for 10 hours, and then calcined. The calcination temperature is selected to be 550°C and the calcination time is 8 hours. Obtain an unmodified catalyst carrier powder.

[0124] The obtained catalyst carrier powder is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor.

[0125] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 500g / l, the carrier modification time is 40 minutes, the calcination and decomposition temperature is 450°C, and the calcination time is 8 hours; a zirconium-modified catalyst carrier is obtained.

[0126] The modified catalyst carrier of step 3 is placed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate impregnation solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier, and the concentration of Ni(NO3)2 in the mixed solution is 600g / l, the concentration of Ce(NO3)3 is 110g / l, the concentration of La(NO3)3 is 120g / l, and the concentration of butanediol is 0.5g / L. The impregnation time is 60 minutes and the impregnation temperature is 55°C.

[0127] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 480°C. The drying time is 10 hours and the calcination time is 7 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0128] The mass percentage of the active component nickel in the obtained catalyst product is 14.6%, the mass percentage of CeO2 is 2.4%, the mass percentage of La2O3 is 1.3%, and the mass percentage of ZrO2 is 3.5%.

[0129] Step 5: Catalyst activity and selectivity evaluation

[0130] Evaluation conditions:

[0131] Heating time: 6 hours

[0132] Catalyst bed temperature: 941℃

[0133] The volume percentage composition of the raw gas is: methane (CH4) 13.1%, carbon dioxide (CO2) 13.3%, carbon monoxide (CO) 17.2%, steam (H2O) 2.4%, hydrogen (H2) 44.1%, and the rest is inert gas.

[0134] Raw gas flow rate: 4250ml / min.

[0135] The evaluation data table is as follows

[0136] Time, h 10 50 100 200 500 800 <![CDATA[CH4 conversion rate, %]]> 97.5 96.2 96.1 95.8 95.6 95.2 <![CDATA[CO2 conversion rate, %]]> 97.5 96.4 96.3 96.2 95.1 94.8 <![CDATA[H2 / CO]]> 1.67 1.67 1.64 1.63 1.63 1.62

[0137] Step 6: Place the catalyst in a fixed bed reactor, pass the raw gas, and conduct a 48-hour high temperature resistance test under high temperature conditions to evaluate the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst in a high temperature environment and the changes in nickel grains.

[0138] The evaluation data table is as follows

[0139] Temperature, °C 800 850 900 950 1000 <![CDATA[NiAl2O4,%]]> -- -- 0.11 0.30 0.40 Ni grain, nm 10 15 18 20 23

[0140] Comparison of Example 1 with Examples 2 to 5 shows that compared with Example 1 in which no polyol is added to the impregnation liquid, after adding polyol alcohol solution to the impregnation liquid in Examples 2 to 5, the catalysts obtained under different experimental conditions can significantly improve the conversion rate of CH4 and CO2 of the finished catalyst. The types of polyols include propylene glycol, ethylene glycol, propylene glycol and butylene glycol.

[0141] Comparison of Example 1 with Examples 2 to 5 shows that compared with Example 1 in which no polyol is added to the impregnation solution, after adding polyol alcohol solution to the impregnation solution in Examples 2 to 5, the catalyst products obtained under different experimental conditions have significantly reduced the amount of nickel aluminum spinel generated under high temperature conditions, and the size of nickel crystals is also significantly reduced, proving that the catalyst products have good high temperature resistance. Types of polyols include propylene glycol, ethylene glycol, propylene glycol and butylene glycol.

[0142] Embodiment 6:

[0143] The present invention provides a method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, comprising the following specific steps:

[0144] Step 1: Take 70% aluminum nitrate and 30% magnesium nitrate hexahydrate according to mass percentage. At a temperature of 50°C, add a certain amount of deionized water to fully dissolve, then add it to the neutralization reaction tank, and then add a sodium carbonate aqueous solution with a mass concentration of 18% for neutralization precipitation, and control the end point pH value to 9.0. The precipitate is filtered and washed, and the filter cake is dried at 115°C for 10 hours, and then calcined. The calcination temperature is selected to be 500°C and the calcination time is 8 hours. Obtain an unmodified catalyst carrier powder.

[0145] The obtained catalyst carrier powder is granulated and pressed into shape after adding a certain amount of release agent, and then calcined again to obtain a catalyst precursor.

[0146] Step 2: Place the catalyst carrier precursor obtained in step 1 in a prepared zirconium nitrate solution for carrier modification. After the carrier modification is completed, dry and calcine the catalyst carrier. The calcination and decomposition can decompose the nitrogen element in the zirconium nitrate to form zirconium dioxide. Zirconium dioxide is distributed on the surface of the catalyst carrier to obtain a modified catalyst carrier, wherein the concentration of Zr(NO3)4 in the zirconium nitrate solution is 400g / l, the carrier modification time is 50 minutes, the calcination and decomposition temperature is 485°C, and the calcination time is 8 hours; a zirconium-modified catalyst carrier is obtained.

[0147] The modified catalyst carrier of step 3 is placed in the prepared nickel nitrate, cerium nitrate and lanthanum nitrate impregnation solution, so that the catalyst active component nickel and the additive are loaded on the catalyst carrier. The concentration of Ni(NO3)2 in the mixed solution is 600g / l, the concentration of Ce(NO3)3 is 110g / l, the concentration of La(NO3)3 is 120g / l, and the concentration of propylene glycol is 0g / L, 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L, 0.1g / L, 2g / L, 5g / L, respectively. The impregnation time is 60 minutes, and the impregnation temperature is 55°C.

[0148] Step 4: The impregnated catalyst carrier is completely dried in a drying furnace at 120°C, and then transferred to a double-channel kiln to calcine and decompose the catalyst carrier loaded with nitrate. The double-channel kiln includes channel A and channel B. The catalyst carrier loaded with nickel nitrate is calcinated and decomposed in channel A using radiant heat at 480°C. The drying time is 10 hours and the calcination time is 7 hours. Finally, the finished catalyst product is obtained. The nitrogen oxide gas generated in channel A is heat-exchanged with the tube of channel B, and then compressed and absorbed by the nitrogen oxide circulating water. The generated nitric acid aqueous solution is used to prepare the nitrate solution to achieve zero emission of nitrogen oxides.

[0149] The mass percentage of the active component nickel in the obtained catalyst product is 14.5%, the mass percentage of CeO2 is 2.3%, the mass percentage of La2O3 is 1.2%, and the mass percentage of ZrO2 is 3.5%.

[0150] Step 5: Catalyst activity and selectivity evaluation

[0151] Evaluation conditions:

[0152] Heating time: 6 hours

[0153] Catalyst bed temperature: 940℃

[0154] The volume percentage composition of the raw gas is: methane (CH4) 13.8%, carbon dioxide (CO2) 13.1%, carbon monoxide (CO) 18.2%, steam (H2O) 2.4%, hydrogen (H2) 43.8%, and the rest is inert gas.

[0155] Raw gas flow rate: 4250ml / min.

[0156] See also Figure 1 , the evaluation data table is as follows

[0157] Propylene glycol, g / l 0 0.1 0.2 0.3 0.4 0.5 0.6 2 5 <![CDATA[CH4 conversion rate, %]]> 93.2 93.5 94.1 97.8 95.1 94.6 93.8 93.2 93.0 <![CDATA[CO2 conversion rate, %]]> 93.5 94.4 95.3 97.2 95.9 95.4 94.0 93.5 93.3 <![CDATA[H2 / CO]]> 1.66 1.67 1.67 1.67 1.66 1.66 1.66 1.67 1.67

[0158] like Figure 1 As shown in the figure. After adding propylene glycol solution to the impregnation solution, the conversion rate of CH4 and CO2 of the finished catalyst can be significantly improved as the concentration of propylene glycol increases. The conversion rate reaches the highest point when the concentration of added propylene glycol reaches 0.3g / L. After that, as the concentration of propylene glycol continues to increase, the conversion rate of CH4 and CO2 of the finished catalyst begins to decrease.

[0159] Step 6: Place the catalyst in a fixed bed reactor and pass the raw gas to conduct a high temperature resistance test at 1000°C for 48 hours to evaluate the effect of the addition of polyols on the high temperature resistance of the catalyst based on the amount of nickel aluminum spinel generated by the catalyst and the change in nickel grains.

[0160] See also Figure 2 , the evaluation data table is as follows

[0161] Propylene glycol, g / l 0 0.1 0.2 0.3 0.4 0.5 0.6 2 5 <![CDATA[NiAl2O4,%]]> 0.99 0.89 0.41 0.38 0.39 0.40 0.65 0.97 0.96 Ni grain, nm 27 26 24 20 20 21 25 26 26

[0162] like Figure 2As shown. After adding propylene glycol solution to the impregnation solution, as the concentration of propylene glycol increases, the amount of nickel aluminum spinel generated in the finished catalyst under high temperature conditions can be significantly reduced, and the size of the nickel grains can be reduced, proving that the finished catalyst has good high temperature resistance. When the concentration of the propylene glycol solution is 0.2-0.5g / l, the effect is best. After that, as the concentration of propylene glycol continues to increase, the amount of nickel aluminum spinel generated in the finished catalyst under high temperature conditions begins to increase, and the size of the nickel grains begins to increase, proving that the high temperature resistance of the catalyst begins to decrease.

[0163] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron, characterized in that: The steps include: S1: Preparation of catalyst support: First, one or more of aluminum nitrate, magnesium nitrate, and calcium nitrate are selected, fully dissolved, and added to a precipitation reaction tank, the temperature of the reaction tank is adjusted, and then a soda ash aqueous solution is slowly added under stirring conditions for neutralization reaction, and the end point PH is controlled to be 7.5-9.5, followed by filtering and washing; the filter cake is dried and then calcined for the first time; the calcined material is added with a release agent and then granulated and formed, and after forming, a second calcination is performed to obtain a catalyst carrier precursor; Step 2: Zirconium dioxide modification: The catalyst carrier prepared in step 1 is placed in a prepared zirconium nitrate solution for carrier modification, and after the carrier modification is completed, the catalyst carrier is dried and calcined to decompose to obtain a modified catalyst carrier; Step 3: Impregnation of active component nickel: A mixed solution of nickel nitrate, cerium nitrate and lanthanum nitrate is prepared to obtain an impregnation solution, and a small amount of polyol solution is added to the impregnation solution; the catalyst carrier modified in step 2 is impregnated in the impregnation solution, so that the catalyst active component nickel and the catalyst promoter are loaded on the catalyst carrier; Step 4: Drying and calcination of the catalyst: The catalyst carrier loaded with nickel nitrate, cerium nitrate and lanthanum nitrate is dried, calcined and decomposed to obtain finished catalyst particles; Step 5: The finished catalyst particles obtained in step 4 are crushed and sieved in a mortar, loaded into a fixed bed reactor, and the activity and selectivity of the catalyst are evaluated; Step 6: Conduct a high temperature resistance test on the catalyst in a fixed bed reactor under high temperature conditions to evaluate the high temperature resistance of the catalyst by observing the formation of nickel aluminum spinel and the changes in nickel grains in a high temperature environment.

2. The method for preparing a zirconium-modified gas-based catalyst for direct iron reduction according to claim 1, characterized in that: In step 2, the concentration of Zr(NO3)4 in the zirconium nitrate solution is 200-600 g / l, the carrier modification time is 10-50 minutes, the calcination decomposition temperature is 300-600°C, and the calcination time is 1-8 hours.

3. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 1, characterized in that: In step 3, the concentration of Ni(NO3)2 in the impregnation solution is 400-800 g / l, the concentration of Ce(NO3)3 is 100-200 g / l, and the concentration of La(NO3)3 is 80-150 g / l.

4. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 3, characterized in that: The impregnation solution contains 0.2-0.5 g / L of polyol.

5. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 4, characterized in that: The polyol is one of ethylene glycol, propylene glycol, glycerol and butylene glycol.

6. The method for preparing a zirconium-modified gas-based catalyst for direct iron reduction according to claim 5, characterized in that: The impregnation solution contains 0.3 g / L of propylene glycol.

7. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 1, characterized in that: Step 4 specifically includes: Step 4.1 is to dry the catalyst using a chain plate drying furnace; Step 4.2, using a hot air circulation double-channel mesh belt furnace to calcine and decompose the catalyst carrier loaded with nitrate, the double-channel mesh belt furnace includes channel A and channel B, channel A is a catalyst decomposition channel, channel B is a hot air circulation channel, which provides a heat source for catalyst decomposition, and the catalyst carrier loaded with nitric acid is calcined and decomposed in channel A, and the high-temperature nitrogen oxide gas generated in channel A is heat exchanged with the tube of channel B, and then enters the nitrogen oxide circulating water absorption device after compression, and the generated nitric acid aqueous solution is used to prepare nitrate solution to achieve zero emission of nitrogen oxides.

8. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 7, characterized in that: A heat exchange tube is provided between channel A and channel B of the double-channel furnace. The heat exchange tube transfers the heat generated by heat exchange in channel B to channel A, providing a heat source for the decomposition of the catalyst in channel A.

9. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 1, characterized in that: In step 5, the activity and selectivity evaluation of the catalyst specifically includes: Step 5.1, heating the catalyst to 500°C under nitrogen, switching to feed gas and continuing to heat to 940°C, with the heating time being no less than 4 hours; Step 5.2, sampling and analyzing the gas composition at the reactor outlet until it is stable; Step 5.3, calculate the conversion rate of carbon dioxide and methane, and the selectivity of carbon monoxide and hydrogen; the conversion rate of carbon dioxide and methane indicates the activity of the catalyst, and the selectivity of carbon monoxide and hydrogen indicates the hydrogen yield of the catalyst and the anti-carbon stability of the catalyst.

10. The method for preparing a zirconium-modified gas-based catalyst for direct reduction of iron according to claim 9, characterized in that: The raw gas is composed of methane, carbon dioxide, carbon monoxide, water vapor, hydrogen and a small amount of nitrogen, wherein the volume percentage of CH4 is 10-15%, the volume percentage of CO2 is 10-15%, the volume percentage of CO is 17-19%, the volume percentage of H2O is 1-5%, the volume percentage of H2 is 40-50%, and the rest is N2.